Investigation of transport phenomena in nano-scale head disk interface - Myo, Kyaw Sett (2017)
Heat-assisted magnetic recording (HAMR) is one of the potential magnetic recording technologies to achieve higher recording capacity and reduce the cost of data storage in hard drives. However, there are many mechanical challenges and difficulties in physical understanding to realize the HAMR for industrial application with stability and reliability. In the HAMR system, a laser beam or other heating sources will be used to heat up the recording medium to reduce the disk media coercivity below the magnetic field applied by a conventional recording head. The heated region in the medium is rapidly cooled to the ambient temperature after the writing process is completed. The head-disk interface (HDI) spacing between the read/write head and the disk is in nanoscale, and it keeps reducing for achieving higher density recording. The involvement of understanding the heat transfer process in the HAMR nano-scale interface becomes important in further developments of this technology. This thesis presents a study to investigate transport phenomena in the head-disk interface of the HAMR system, including the air bearing, the heat generation and the heat transfer at the interface. Firstly, the slider air bearing that supports a slider floating above a disk is modeled and studied using the Reynolds’ equations based model. The direct Monte Carlo simulation (DSMC) method is then introduced to apply in the HAMR air bearing study, taking into account of thermal effect. The DSMC simulation results of the slider bearing characteristics are obtained with various slider postures and utilized for verifying those from the traditional continuum-based model. This is a pioneer research work in applying the DSMC method to solve HAMR air bearing problems. It is found that the presence of localized laser heating process could increase the air bearing pressure acted to the slider surface and affect the slider flying behaviors. Secondly, the heat generation resulted from the laser delivery system, which is supposed to be designed inside an integrated HAMR slider body, could cause the slider’s temperature rise and thermal protrusion. This heat transfer process is examined by the finite element method using the ANSYS software in modeling and analyzing the thermal distribution of a HAMR slider. The numerical results predict that the heat dissipations in optical components of an integrated HAMR slider could lead to the contact between the flying head and disk, consequently causing the HAMR hard drive failure. Thirdly, the HAMR recording disk is designed as the multi-layered format in order to achieve the desired temperature in a recording media layer while the data is being written or stored at the respective frequency. The heat transfer process in the disk is studied with the energy transformation models to obtain the disk surface temperature with a localized hot spot. The laser beam will also heat the air in the head disk interface region and its effect on the slider air bearing could influence the drive’s reliability. This is due to the high disk-surface temperature at the localized laser-heating region, which could create the variation of gas properties and affect the surrounding components in the interface. As the interface region is nanoscale, the heat transfer in this region involves the thermal radiation between a slider and a disk. Therefore, a new heat transfer model is developed, which takes into account of the radiation effect associated with the slider temperature and its surface profile. By applying this new heat transfer model, more accurate slider temperature and protrusion profiles could be predicted under the slider flying condition in the HAMR system. Consequently, by comprehending thermal conditions and their effects in HAMR HDI, it could help in designing a proper air bearing surface (ABS) and enhancing the reliability of HDI to contribute in thriving for the HAMR technology as a next generation hard drive technology.